Analysis of the Impact of Bullying on Students' Social Interactions at Malahayu 03 Public Elementary School (International Journal of Education and Literature, 2025)
This research was conducted at Malahayu 03 Elementary School, Brebes Regency. The objectives of this research are (1) To describe the impact of bullying on students' social interactions (2) To describe the factors that influence students' social interactions after experiencing bullying. This type of research uses Qualitative research using interview and Documentation techniques. Based on the results of research conducted through interviews, observations, and documentation at Malahayu 03 Elementary School, it can be concluded that bullying has a significant impact on students' social interactions, especially for victims. These impacts can be seen in the following aspects: (1) Emotional and psychological: Students who are victims of bullying show symptoms such as feelings of worthlessness, prolonged sadness, fear of expressing opinions, and experiencing pressure to be accepted by the group. (2) Decreased social interaction: Victims tend to be alone, avoid group activities, and withdraw from the social environment of the class. (3) Decrease in academic achievement: It was found that victims of bullying experienced a decline in academic grades and difficulty concentrating while studying, as a result of the mental pressure they experienced. (4) School environment: The existence of a culture of seniority and the lack of serious handling by the school towards perpetrators of bullying causes victims to feel increasingly unsafe.